Ergonomics analysis of muscle activity of workers in a metal stamping industry / Md Fuad Bahari ... [et al.] - Bahari, Md Fuad; Omar, Abdul Rahman; Solomon, Darius Gnanaraj; Saad, Nor Hayati; Halim, Isa (Institute of Research, Development and Commercialisation (IRDC), 2006)
Occupational health is considered as a crucial element in almost every Small and Medium Industries (SMIs) and it is believed to be one of vital challenges that can influence productivity and competitiveness. It has been known that the metal stamping industry involved a lot of materials handling tasks such as carrying stamped parts from machine to packaging section, transferring moulds from tools store to machines, sorting the finished products and others. Appropriate materials handling equipments are not often provided in SMIs because of the limitation of capital and lack of ergonomics awareness. The workers have to handle the materials and goods manually. These practices may lead to occupational injuries particularly back pain and musculoskeletal injuries. The objectives of the research are to assess and analyze the muscles activity of workers in metal stamping industry. Three male workers who performed metal stamping process using manual technique were participated in the research. Ergonomic assessment associated with Surface Electromyography (SEMG) was used to capture and interpret the data related to muscles activity at before and after the ergonomic intervention. For the purpose of muscle activity assessment, SEMG electrodes were attached to eight critical muscles: deltoid muscle-medial part (left), deltoid muscle-medial part (right), trapezius muscle (left), trapezius muscle (right), erector spinae muscle (left), erector spinae muscle (right), gastrocnemius muscle (left) and gastrocnemius muscle (right). An ergonomically designed workstation has improved working posture and reduced the total muscle work/loading by about 43 % if it is properly utilized. This design approach can be adopted to improve the working conditions of industrial workers and thus enhance the occupational health practices.